Kolb’s Experiential Learning Model as a Conceptual Framework for Visual Research in Rural Tourism Sites: Batuh Narit Arur Bilit as a Case Study - Sarah Naemah, Aman Leong; Yakup, Mohd Rafee; Doris, Maying; Hishamuddin, Siri; Awangko Hamdan, Awang Arshad; Sylvester Wielding, Jussem (Faculty of Economics and Business, Universiti Malaysia Sarawak, 2019)
This paper demonstrates the implementation of Kolb’s experiential learning model (ELM), a learner-centric learning method that often used in classrooms and organizational training as a method of research on the visual aspects of rock carving named Batuh Narit Arur Bilit in Kelabit Highlands, Sarawak. This study will highlight thoroughly on the visual research process of Batuh Narit Arur Bilit from acquiring to the interpretation of data to be suited into ELM. The research of visuals in culture is usually conducted in visual anthropology method, however, this practice is often time-consuming, and visuals only serve as a tool to document and describe, but not as a subject of research. The method involves a systematic, stage by stage process of recording visual images, observation, sense of touch, transferring images into digital format, and presenting the outcomes to the public. ELM does not just offer an organized method of collecting and analyzing data in a short period but has also contributed in establishing a dialogue between researchers and the public, especially the local community and thus benefit both parties. The versatility of ELM will hopefully benefit more visual researchers in conducting research within a short period as an alternative to visual anthropology method.